Local Wisdom Integration in Picture Storybooks for Elementary School Reading Comprehension: A Systematic Literature Review - Lestari, Eka Yuni; Suryanti, Suryanti; Suprapto, Nadi (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This systematic literature review examines the integration of local wisdom into picture storybook media to enhance Reading comprehension among elementary school students. The study synthesizes findings from 24 peer-reviewed articles published between 2020 and 2025, focusing on the effectiveness, pedagogical advantages, and implementation challenges of culturally responsive picture storybooks in Indonesian elementary education contexts. The review follows PRISMA guidelines for systematic review, examining studies that integrate local cultural elements, including folklore, traditional values, and regional narratives, into visual storytelling materials. Findings indicate that picture storybooks embedded with local wisdom consistently demonstrate significant improvements in Reading comprehension, with effect sizes ranging from medium to large across various studies. The integration of familiar cultural contexts enhances student engagement, motivation, and understanding of the context of Reading materials. Key advantages include increased relevance to students’ lived experiences, strengthened cultural identity, and improved literacy outcomes across diverse demographic settings. However, limitations persist in terms of geographical scope, scalability challenges, and the need for sustained teacher professional development. This review contributes to the growing body of evidence supporting culturally responsive teaching approaches in literacy education. It provides recommendations for researchers, educators, and policymakers seeking to implement culturally grounded Reading materials in elementary education settings.